Rhinocricidae Systematics II: A species catalog of the Rhinocricidae (Diplopoda: Spirobolida) with synonymies - Marek, Paul E.; Bond, Jason E.; Sierwald, Petra (Zootaxa, 2003)
This paper summarizes the distribution, provides a taxonomic bibliography from 1758 to 2002, and lists all available species, generic names, and synonymies of the family Rhinocricidae (Diplopoda: Spirobolida). At present, there are 528 nominal species and 23 subspecies of Rhinocricidae placed in 27 genera and 3 subgenera. One new combination is proposed: Rhinocricus obesus rubicundus is transferred to Anadenobolus [Anadenobolus obesus rubicundus (Brölemann, 1905)].